Diskursetnologiska utmaningar: Från politisk teori till empirinära kulturforskning – och vidare - Gunnarsson Payne, Jenny (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
What does discourse theory “do” to ethnology? And complementarily, what does ethnology “do” to discourse theory? In this article, these two questions are approached by investigating how Swedish ethnologists have hitherto described and applied discourse theory. The article identifies a couple of overarching tendencies within Swedish discourse theoretical ethnology, relating these tendencies both to other intra disciplinary trends and to parallel international developments of applied discourse theory. Specifically, the article will discuss current ethnological interpretations and applications of the concept of discourse as well as the discourse theoretical understanding of the subject, and will furthermore argue that these theoretical ideas still harbour underutilized possibilities, opportunities that, if taken, might serve to further develop discourse theoretical ethnology.